Improved outcomes over time and higher mortality in CMV seropositive allogeneic stem cell transplantation patients with COVID-19; An infectious disease working party study from the European Society for Blood and Marrow Transplantation registry - Ljungman, Per; Tridello, Gloria; Piñana, Jose Luis; Ciceri, Fabio; Sengeloev, Henrik; Kulagin, Alexander; Mielke, Stephan; Yegin, Zeynep Arzu; Collin, Matthew; Einardottir, Sigrun; Lepretre, Sophie Ducastelle; Maertens, Johan; et al. (Frontiers in Immunology, 2023)
COVID-19 has been associated with high morbidity and mortality in allogeneic hematopoietic stem cell transplant (allo-HCT) recipients. This study reports on 986 patients reported to the EBMT registry during the first 29 months of the pandemic. The median age was was 50.3 years (min – max; 1.0 – 80.7). The median time from most recent HCT to diagnosis of COVID-19 was 20 months (min – max; 0.0 – 383.9). The median time was 19.3 (0.0 - 287.6) months during 2020, 21.2 (0.1 - 324.5) months during 2021, and 19.7 (0.1 – 383.9) months during 2022 (p = NS). 145/986 (14.7%) patients died; 124 (12.6%) due to COVID-19 and 21 of other causes. Only 2/204 (1%) fully vaccinated patients died from COVID-19. There was a successive improvement in overall survival over time. In multivariate analysis, increasing age (p<.0001), worse performance status (p<.0001), contracting COVID-19 within the first 30 days (p<.0001) or 30 – 100 days after HCT (p=.003), ongoing immunosuppression (p=.004), pre-existing lung disease (p=.003), and recipient CMV seropositivity (p=.004) had negative impact on overall survival while patients contracting COVID-19 in 2020 (p<.0001) or 2021 (p=.027) had worse overall survival than patients with COVID-19 diagnosed in 2022. Although the outcome of COVID-19 has improved, patients having risk factors were still at risk for severe COVID-19 including death.